Pengaruh Metode Evaluasi Pembelajaran Terhadap Motivasi Mahasiswa Pendidikan Karakter Program Studi Guru Sekolah Dasar Universitas Tribuana Kalabahi - Selly, Alboin (Jurnal Ilmiah Wahana Pendidikan, 2026)
Learning evaluation is a crucial component of the educational process because it measures the success of the learning process and provides feedback for developing teaching methods. In the context of higher education, the evaluation methods implemented by lecturers not only serve as a measure of academic achievement but can also influence student learning motivation. This study aims to analyze the influence of learning evaluation methods on student learning motivation in the Character Education course in the Elementary School Teacher Education (PGSD) Study Program at Tribuana Kalabahi University. This study used a quantitative approach with a survey method. The study population was all 170 second-semester PGSD students. The sample was determined using proportional random sampling, with 119 respondents. Data collection was conducted using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The results showed that learning evaluation methods, including independent assignments, class presentations, midterm exams (UTS), and final exams (UAS), simultaneously had a significant effect on student learning motivation. Partially, independent assignments, class presentations, and final exams significantly influenced student learning motivation, while midterm exams showed no significant effect. The coefficient of determination of 0.781 indicates that 78.1% of the variation in student learning motivation can be explained by the learning evaluation method used in this study. The findings of this study confirm that participatory learning evaluation methods that encourage active student involvement contribute significantly to increasing learning motivation compared to conventional evaluation methods. Therefore, lecturers are expected to develop more innovative and student-centered learning evaluation strategies.